Reciprocity in the Clubhouse Context - Tanaka, Kimiko (International Journal of Psychosocial Rehabilitation, 2015)
Albeit still limited, the literature has begun to document reciprocity, including service user-provider reciprocity, as key to psychiatric recovery. This article presents a thick description of reciprocity occurring in the mental health clubhouse con- text, drawing on qualitative interview data from 103 users and 25 staff at five clubhouses in the U.S. and Finland, which was analyzed using a grounded theory approach. We found that receiving and giving support appears to be a part of every- day life at the clubhouse. We also found that this seemed conducive to recovery in that it helped users, through what we identified as clubhouse ways, to experience personhood, thereby transforming their battered sense of existence into a sense of agency and, perhaps more importantly, a sense of self-worth and being part of society. The clubhouse model may repres- ent a viable collective approach to complement current community-based mental health systems of care that emphasize in- dividual support.